Fluorescence Localization and Comparative Ultrastructural Study of Periplocoside NW from Periploca sepium Bunge in the Midgut of the Oriental Amyworm, Mythimna separata Walker (Lepidoptera: Noctuidae) - Feng, Mingxing (MDPI, 2014)
Periplocoside NW (PSNW) is a novel insecticidal compound isolated from the root bark of Periploca sepium Bunge and has potent stomach toxicity against some insect pests. Previous studies showed that the Mythimna separata larva is sensitive to PSNW, but the Agrotis ispilon larva is insensitive. In this study, preliminary target localization on the midgut of M. separata larvae was conducted via a fluorescence labeling technique. A comparative ultrastructural study on the effects of PSNW on the midguts of M. separata and A. ispilon larvae was performed. Symptom observation results showed that typical stomach toxicity was induced by PSNW in M. separata larvae. Fluorescence localization results showed that PSNW binds to the midgut cells of M. separata larvae. Ultrastructure observations showed destruction of the microvilli, organelle, and cytomembrane in the midgut cells of M. separata larvae, whereas no obvious changes were observed in midgut cells of A. ispilon larvae. These results were consistent with the insecticidal activity of PSNW. Therefore, PSNW might act on the midgut tissues of the insects, and one or more binding sites of PSNW may exist in M. separata larvae midgut cell cytomembranes.